Description of a new species of Neoromicia (Chiroptera: Vespertilionidae) from southern Africa: A name for “N. cf. melckorum” - Goodman, Steven M.; Kearney, Teresa; Ratsimbazafy, Malalatiana Michèle; Hassanin, Alexandre (Zootaxa, 2017)
The taxonomy of sub-Saharan small insectivore bats of the family Vespertilionidae is unresolved and currently five named species of the genus Neoromicia are recognized from southern Africa, with N. melckorum considered a synonym of N. capensis. Since several years, the name “N. cf. melckorum” has been used in the literature to designate an apparently undescribed and moderately large bodied vespertilionid bat known from different localities in southern and southeastern Africa. Using new data from molecular genetics, bacular morphology, and cranio-dental characters, we conclude that N. melckorum sensu stricto is indeed nested within N. capensis and obtain the needed evidence to formally describe “N. cf. melckorum”, named herein as N. stanleyi sp. nov. On the basis of molecular and bacular evidence, N. stanleyi is found in Botswana, Zimbabwe, and Zambia, and using a combination of other characters is presumed to occur in northern South Africa and Malawi. Bayesian and maximum likelihood analyses based on 12S rRNA sequences indicate that it belongs to a clade containing four species of Neoromicia (N. capensis, N. malagasyensis, N. matroka, and N. robertsi) and Laephotis. Neoromicia stanleyi shows at least 3.2% nucleotide divergence from its closest relatives. It is larger in cranial characters than other members of the capensis group occurring in the southern portion of Africa, and a number of bacular characters distinguish N. stanleyi from N. capensis.